Evaluation of the efficacy and tolerance of Soyfem in women in the early menopausal period - Stanosz, Stanisław; Puk, Ewa; Grobelny, Włodzimierz; Stanosz, Małgorzata; Kazikowska, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2006)
Objective: The evaluation of efficacy and tolerance of using Soyfem in women in the early postmenopausal period treated with the drug for 12 months. Design: 71 women in the early postmenopausal period were randomized and assigned to one of three groups: group I treated with 2 tablets of placebo twice a day (n=23); group II treated with 1 tablet of the Soyfem preparation and 1 tablet of placebo twice a day (n=26; 200 mg of extract, i.e. 52 mg of genistein); group III treated with 2 tablets of the Soyfem preparation twice a day (n=22; 400 mg of extract, i.e. 104 mg of genistein). The frequency and intensity of menopausal signs were evaluated using the Kupperman test every 30 days for 12 months. Statistical analyses of evaluated parameters were made using Statistica PC, StatSoft. Results: Treatment with the Soyfem preparation leads to a significant decrease of the frequency and intensity of menopausal signs after 3 months of therapy with the higher drug dosage (p<0.02). After 12 months of therapy, a total or an almost total (90-100%) reduction of unpleasant signs in both groups was observed. Conclusion: This clinical trial showed that the Soyfem preparation has a positive influence on the frequency and intensity of menopausal signs, with a statistically significant reduction of 10 menopausal signs after the 3rd month of the 12-month administration period. Soyfem belongs to effective, well-tolerated medical preparations with a positive safety profile.